COMPARISON OF THE EFFECT OF DIFFERENT MESH IMPLANTS ON THE REPRODUCTIVE SYSTEM IN EXPERIMENTAL MODELS OF GYNECOLOGICAL SURGERIES - Safonov, R.A.; Prokopiuk, V.Yu.; Prokopiuk, O.V.; Lazurenko, V.V.; Tishchenko, O.M.; Ovcharenko, O.B. (World of Medicine and Biology, 2022)
Genital prolapse complicates the lives of many women after the age of 50. The use of mesh implants is a promising method of surgical correction of this disease. The study on mice compared the effect of the most common surgical meshes on the morphofunctional state of the reproductive system of animals, the postoperative period, and the completeness of morphological and functional recovery of the defects in the lower abdominal wall. It was found that thinner meshes cause less inflammatory reactions, faster recovery and less atrophic phenomena in the internal genitals. The recovery rate also depends on the material and structure of the mesh.
Keywords: gynecological surgeries; surgical meshes; genital prolapse; uterus; ovaries